Towards the exploitation of project – based learning for group work activities to enhance the English speaking skill of the third – year English majored students at Hong Duc University - Lê, Thị Thanh Hương (University of Languages and International Studies, 2017)
Focusing on learning and teaching English speaking skill at the Foreign Language Department, Hong Duc University, this action research is aimed at working out an effective supplementary learning activity to improve students’ speaking competence. After carrying out preliminary investigation and literature review, it is found out that project based learning is one of the effective methods used largely by teachers to teach speaking skill in English language learning. M.A Thesis English Teaching Methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2014